Pseudo‐Halide Perovskite Solar Cells. Issue 28 (9th June 2021) - Lin, Pei‐Ying; Loganathan, Aswaghosh; Raifuku, Itaru; Li, Ming‐Hsien; Chiu, Yueh‐Ya; Chang, Shao‐Tung; Fakharuddin, Azhar; Lin, Chen‐Fu; Guo, Tzung‐Fang; Schmidt‐Mende, Lukas; Chen, Peter
Abstract: Perovskite solar cells (PSCs) have achieved certified power conversion efficiency (PCE) over 25%. Though their high PCE can be achieved by optimizing absorber layer and device interfaces, the intrinsic instability of perovskite materials is still a key issue to be resolved. Mixed‐halide perovskites using multiple halogen constituents have been proved to improve robustness; however, the anion at the X site in the ABX3 formula is not limited to halogens. Other negative monovalent ions with similar properties to halogens, such as pseudo‐halogens, have the opportunity to form perovskites with ABX3 stoichiometry. Recently, thiocyanates and formates have been utilized to synthesize stable perovskite materials. This review presents the evolution of pseudo‐halide perovskite solar cells in the past few years. The intrinsic properties, their effects on crystal structure, and bandgap engineering of the pseudo‐halide perovskites are summarized. Various thiocyanate compounds applied in the fabrication of perovskite solar cells are discussed. The fabrication process, film formation mechanism, and crystallinity of pseudo‐halide perovskites are elucidated to understand their effects on the photovoltaic performance and device stability. Other applications of pseudo‐halide perovskites are summarized in the final section. Lastly, this review concludes with suggestions and outlooks for further research directions. Abstract : Monovalent pseudo‐halide anions share similar properties to halide anions. This review presents the evolution of pseudo‐halide perovskite solar cells in the past few years. The role of pseudo‐halides and their position and occupation in perovskite crystal, its impact on perovskite film quality, solar cell stability and photovoltaic performance, and pseudo‐halide optoelectronic devices beyond solar cells are compared comprehensively.